2021
DOI: 10.1038/s41467-021-26272-1
|View full text |Cite
|
Sign up to set email alerts
|

Three chromosome-level duck genome assemblies provide insights into genomic variation during domestication

Abstract: Domestic ducks are raised for meat, eggs and feather down, and almost all varieties are descended from the Mallard (Anas platyrhynchos). Here, we report chromosome-level high-quality genome assemblies for meat and laying duck breeds, and the Mallard. Our new genomic databases contain annotations for thousands of new protein-coding genes and recover a major percentage of the presumed “missing genes” in birds. We obtain the entire genomic sequences for the C-type lectin (CTL) family members that regulate eggshel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 95 publications
1
51
0
Order By: Relevance
“…The apparent discordance remained a major evolutionary conundrum. Some studies have shown that birds tend to have fewer genes than other tetrapods due to the large segmental deletions found in their genomes ( Lovell et al 2014 ; Zhang et al 2014 ), whereas other researchers suggested that these missing genes may not have been sequenced ( Bornelöv et al 2017 ; Botero-Castro et al 2017 ; Yin et al 2019 ; Zhu et al 2021 ). Using more advanced sequencing technologies and methodologies, the Vertebrate Genomes Project (VGP) found many genes were missing in previous genome assemblies, and this was clearly not a biological difference as some of the previous and VGP assemblies were from the same individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent discordance remained a major evolutionary conundrum. Some studies have shown that birds tend to have fewer genes than other tetrapods due to the large segmental deletions found in their genomes ( Lovell et al 2014 ; Zhang et al 2014 ), whereas other researchers suggested that these missing genes may not have been sequenced ( Bornelöv et al 2017 ; Botero-Castro et al 2017 ; Yin et al 2019 ; Zhu et al 2021 ). Using more advanced sequencing technologies and methodologies, the Vertebrate Genomes Project (VGP) found many genes were missing in previous genome assemblies, and this was clearly not a biological difference as some of the previous and VGP assemblies were from the same individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic rearrangements, particularly inversions, have played important roles in the local adaptation and speciation of birds ( Jiang et al 2021 ; Li et al 2021 ; Zhu et al 2021 ). The orientations of syntenic regions were further classified into inversions for each pairwise genome comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al, 2020). The recent availability of a large number of bird genomes (Zhang et al, 2014a) and improved quality of the representative genomes from several clades of birds (Warren et al, 2017; Zhu et al, 2021) have allowed the detailed comparative investigation of bird genomes (Ellegren, 2013). For instance, the loss of RIG-I in the chicken while being functional in the duck has provided insights into the differential response of these bird species to various pathogens (Barber et al, 2010).…”
Section: Discussionmentioning
confidence: 99%